(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Thyreophora is a taxon of dinosaurs composed of Stegosauria and Ankylosauria, whose members have been known to utilise their tails as powerful defensive weapons. Remains of these dinosaurs are scarce; the Portuguese taxon, Miragaia longicollum, known from three individuals, provides precious pieces of information on the anatomy of these rare animals. This study estimates the stress resistance of a stegosaurian tail and uses Multi-Body Dynamics Analysis (MBDA) to properly simulate the movements of the tail of M. longicollum. The results show that the tail of M. longicollum can achieve high speeds and generate significant pressures, akin to those observed in other tyreophoran dinosaurs. Such high speeds would potentially generate powerful strikes and would inflict injuries on predators. However, the caudal spines of M. longicollum, despite being larger than those of Stegosaurus stenops, have worse stress-bearing performances than those of S. stenops, due to their different morphology. Investigating the complex biomechanics governing the tail of a dinosaur, such as M. longicollum, can have significant implications across various disciplines. Investigating biomechanics in extinct species offers valuable insights into comparative anatomy and physiology, facilitating connections between ancient and contemporary life forms. Palaeontologists and evolutionary biologists might use this information to better comprehend the dinosaur movement, which would advance our understanding of ancient ecosystems and have an impact on how we interpret the behaviour of contemporary animals. The knowledge obtained from such study might provide useful biomimicry lessons for robotics engineers, serving as inspiration for the creation of more adaptable and agile robotic systems.